KARAKTERISTIK DAN UTILISASI PEKTIN KULIT SEMANGKA (CITRULUS LANATUS): TINJAUAN SISTEMATIK - Kaneth (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Watermelon (Citrullus lanatus) peels are one of the major solid wastes that can result in environmental problems. Watermelon peels contain a high amount of pectin, a polysaccharide with various functional properties. Extracting pectin from watermelon peels may be valuable for various industrial applications, especially in the food industry. This systematic review aims to summarize the characteristics of watermelon peel-derived pectin and its potential utilization in the food industry. This systematic review was made using the PRISMA guidelines as its basis. The author performed the literature research using Science Direct, Taylor & Francis, EBSCOHost, and SAGE journals databases. This systematic review provides a comprehensive review of 11 studies focusing on the characteristics and utilization of watermelon peel pectin (WPP). The result of the systematic review shows that the extraction method and conditions can greatly affect the characteristics of the resulting WPP. Under similar acidic conditions as commercial pectin, WPP exhibits desirable key characteristics, such as high methoxy and protein content, high degree of esterification, high AUA content, and low degree of methylation. These characteristics makes WPP have an excellent emulsifying, foaming, and gelling properties. Therefore, it is important to determine a suitable extraction method to produce WPP with a desirable properties for the utilization in the food industry.